2004
DOI: 10.1152/ajpendo.00149.2003
|View full text |Cite
|
Sign up to set email alerts
|

NO plays a role in LPS-induced decreases in circulating IGF-I and IGFBP-3 and their gene expression in the liver

Abstract: Priego, Teresa, Inmaculada Ibáñez de Cáceres, Ana Isabel Martín, M. Á ngeles Villanú a, and Asunción López-Calderón. NO plays a role in LPS-induced decreases in circulating IGF-I and IGFBP-3 and their gene expression in the liver. Am J Physiol Endocrinol Metab 286: E50-E56, 2004. First published September 16, 2003 10.1152/ajpendo.00149.2003In this study, we administered aminoguanidine, a relatively selective inducible nitric oxide synthase (iNOS) inhibitor, to study the role of nitric oxide (NO) in LPSinduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
3
17
0
3
Order By: Relevance
“…This effect might be due, in part, to the inhibitory effects of dexamethasone on NO production, since dexamethasone decreased the expression of iNOS in hepatocytes (Geller et al 1993). In addition, in the present study we found that dexamethasone pretreatment blocked the increase in circulating nitrite and nitrate concentrations in LPS-treated rats, and furthermore, we have shown that iNOS inhibition attenuated the inhibitory effect of LPS on hepatic IGFBP-3 mRNA levels (Priego et al 2004). …”
Section: Figuresupporting
confidence: 72%
See 2 more Smart Citations
“…This effect might be due, in part, to the inhibitory effects of dexamethasone on NO production, since dexamethasone decreased the expression of iNOS in hepatocytes (Geller et al 1993). In addition, in the present study we found that dexamethasone pretreatment blocked the increase in circulating nitrite and nitrate concentrations in LPS-treated rats, and furthermore, we have shown that iNOS inhibition attenuated the inhibitory effect of LPS on hepatic IGFBP-3 mRNA levels (Priego et al 2004). …”
Section: Figuresupporting
confidence: 72%
“…This mechanism could involve NO, since dexamethasone pretreatment prevents the increase in serum nitrite and nitrate concentrations in LPS-treated rats. Moreover, we have previously reported (Priego et al 2004) that inhibition of iNOS by aminoguanidine administration prevented the effect of LPS on circulating IGF-I and its gene expression in the liver as well as on circulating nitrite and nitrate concentrations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus the ability of gadolinium to prevent LPS-induced increase in serum concentrations of nitrite/nitrate can be the result of blocking iNOS induction in several tissues. We have previously observed that inhibition of iNOS by aminoguanidine treatment prevents LPS-induced decrease in IGF-I and IGFBP-3 gene expression in the liver (Priego et al 2004). Therefore, prevention of iNOS induction and nitric oxide release in the liver may be one of the possible mechanisms by which gadolinium administration prevents the effect of LPS on serum and liver IGF-I and IGFBP-3.…”
Section: Discussionmentioning
confidence: 98%
“…Induction of inducible nitric oxide synthase (iNOS) during sepsis is involved in the inhibition of IGF-I-IGFBP-3 after LPS administration (Priego et al 2004).…”
Section: Introductionmentioning
confidence: 99%